HUBUNGAN KARAKTERISTIK INDIVIDU DAN BEBAN KERJA DENGAN GEJALA SICK BUILDING SYNDROME PADA KARYAWAN PT. INFOMEDIA NUSANTARA TAHUN 2020 - Aulia Nursyafitri Chotimah (2020)
Over the past few years, the term Sick Building Syndrome has become more common but not everyone is clear about what it really is. Sick Building Syndrome is described as a situation where more than 20% of building occupants complain about air quality or have persistent symptoms. Elsewhere, such as in major cities in Indonesia, the possibility of Sick Building Syndrome is high because there are many building constructions without considering health factors. Poor air circulation in the office room causes a dangerous working environment that makes employees increasingly sick as time goes by. This study aimed to determine the relationship between individual employee characteristics and workload with Sick Building Syndrome symptoms on employees of PT. Infomedia Nusantara in 2020. Sample selection technique by total sampling and a sample size of 72 respondents using cross sectional method. Data collection using questionnaire aids. The results of data collection will be analyzed univariate and bivariate. The results revealed that there were a relationship between age (p = 0.029), psychosocial condition (p = 0041), and occupational stress (p = 0.021) with Sick Building Syndrome symptoms. Whereas no relationship was found for other variables such as gender, work period, disease history, and workload. Suggestions that can be undertaken are to implement medical check-up programs periodically, make the work environment ideal and conducive, and provide them with health clinics.